الهدف العسكري المشروع واهم المباديء التي تحكمه في القانون الدولي الانساني - محمود, لمى عبد الباقي; محمد, مروة ابراهيم (Journal of Legal Sciences, 2019)
The direct military attacks in international armed conflicts may be against military targets Oalohdav and civilian objects alike, and so these attacks are legitimate, so do not result in an international responsibility, must be directed to the legitimate military targets without objects and civilian objects, and then may ask international law two conditions in these goals even can be counted legitimate military objectives may strikes her, the two effective contribution to military action, and to achieve a definite military advantage when directing attacks against it, and most of the development of international humanitarian law legal principles that limit the persistence of hostile forces to strike and attack targets and objects without distinction, so as not to attack these targets, damage to civilians and civilian objects, and perhaps the most prominent of these principles, the principle of distinction, which requires the distinction between civilians and combatants and between civilian objects and military dignitaries, and the principle of proportionality between the generated feature or desired investigation of the attack and damage and its expected impact on civilians and the environment